Cultivating usage and word-of-mouth in food delivery applications: a conceptual study / Nurul Syahirah Idris, Dr. Muhammad Safuan Abdul Latip and Ts. Dr. Noradzhar Baba - Idris, Nurul Syahirah; Abdul Latip, Muhammad Safuan; Baba, Noradzhar (Universiti Teknologi MARA, Kedah, 2024)
Food delivery applications (FDAs) have surged in popularity in recent years, gaining widespread acceptance among consumers in both developed and developing countries. The appeal of these applications stems from their user-friendly interfaces and efficient food delivery services to people's homes. FDAs have also offered restaurants a unique opportunity to boost revenue without expanding seating capacity. The food sector transformed as busy consumers increasingly use FDAs due to hectic schedules, impacting dining and cooking habits. Despite the escalating popularity of FDAs, a need remains to comprehend the drivers of their usage and electronic word-of-mouth across various age groups and generations. Hence, this study seeks to conduct an in-depth literature review to explore the potential factors influencing FDA usage and eWOM. The Technology Acceptance Model (TAM) is utilised as a guiding framework to underpin the rationale behind potential predictors, providing insights to practitioners and academics in the food delivery industry, thereby enhancing urban landscape planning and management efficiency. Additionally, the study aims to conceptually investigate potential connections between FDA users and demographic characteristics, uncovering potential differences. The study's findings are intended to offer valuable insights to practitioners and researchers within the food delivery sector, fostering a deeper understanding of the drivers behind food delivery app adoption and eWOM, with a clear focus on demographic distinctions.